A novel c.287G>T NDP missense mutation in a Chinese family with Norrie disease. (3rd July 2020) - Lin, Meina; Lu, Yongping; Sui, Yu; Ni, Xiang; Li, Huan; Chen, Xinren; Zhao, Ning; Jiang, Miao
ABSTRACT: Background: Norrie disease is a rare X-linked recessive disorder in affected males. The typical features are congenital blindness, progressive hearing impairment, and, in some cases, some degree of mental retardation, microphthalmia, microcornea, growth failure, and seizures. Norrie disease is caused by mutations in the Norrie disease pseudoglioma gene ( NDP), which encodes the Norrin protein that plays a crucial role in vascular development, neural cell differentiation, and proliferation in the retina and cerebellum. The aim of the present study was to identify the genetic cause of the disease and the phenotypic characteristics of the patients in an affected Chinese family. Materials and Methods: A Chinese family with Norrie disease was studied, and clinical phenotypes of the proband were observed. With informed consent from the patients' family, blood samples from family members were collected, genomic DNA was extracted, and Sanger sequencing was performed to identify the disease-causing mutation. Re: sults : The c.287 G > T mutation of NDP was identified by Sanger sequencing and resulted in p.Cys96Phe. The pathogenicity prediction was performed by MutationTaster, Polyphen-2, SIFT, and PROVEAN, all of which suggested that the mutation is disease-causing and may be responsible for the phenotypes of Norrie disease. Conclusion: The c.287 G > T of NDP is a novel mutation responsible for Norrie disease in a Chinese family.